User interface design for children and youth : websites and applications to promote mental health and wellbeing - Mehtälä, Saana (2018)
This master’s thesis focuses on the design of digital mental health and wellbeing websites and applications for children and youth. First, a literature review was carried out to identify the most important theories and recent research efforts within this field. The subject was inspected from the perspective of child and youth user interface (UI) design. According to the reviewed literature, digital mental health and wellbeing resources generally lack research evidence to support their effectiveness. In terms of UI design, the resources should be more carefully designed in order to be more suitable to child and youth users. For example, efforts to make websites, applications and games to support the intrinsic motivation of children and youth could enhance the achievement of the underlying mental health and wellbeing outcomes. As a result, a framework for assessing the suitability of mental health and wellbeing resources for children and youth was created. In the second phase of the thesis, a heuristic evaluation was carried out to assess how well the existing digital mental health and wellbeing resources (n=49) follow the principles presented in the framework. The main findings include how most of the mental health and wellbeing resources assessed have difficulties with content, social interaction, user engagement, co-design and information privacy. The providers of child and youth mental health and wellbeing websites and applications should pay more attention to adequately narrowing down their intended target group, while providing wider possibilities for social interaction. In addition, user engagement should be better promoted by increasing the provision of narrative, gamification and interactive elements. Finally, co-design processes used should be made more specific and visible to the user. The quality of data privacy statements should also be improved by more clearly stating the information processing practices relating to both personal and non-personal data. In conclusion, the existing digital mental health and wellbeing websites, as well as applications do not meet most of the design principles set for children and youth to an adequate standard.